Pemahaman tentang Munculnya Pejuang Teroris Asing Indonesia: Ekonomi Politik, Analisis Pasar, dan Pendekatan Teori Perubahan - Bramantyo, Muhammad Hilmy (Pusat Pelaporan dan Analisis Transaksi Keuangan (PPATK), 2023)
The issue of terrorism in Indonesia has escalated from causing problems in its home country to other countries. These new groups of terrorists are called Foreign Terrorist Fighters (FTFs). The qualitative method used in this paper to analyse the emergence of Indonesian FTFs to Syria to fight alongside the Islamic State of Iraq and Syria (ISIS) by using the theoretical framework of Political Economy Analysis (PEA), Market Analysis (MA), and Theory of Change. By using PEA, it could be argued that at the macro, sectoral, and micro levels, the emergence of Indonesian FTFs is inevitable. The use of MA also supports the emergence of Indonesian FTFs and how to intervene in them. Finally, this paper argued the theory of change to stop the flow of Indonesian FTFs, namely deterrence for supporters of Indonesian FTFs, communicate effectively with people influenced by terrorist doctrine, and change the culture by redefining the concept of jihad and applying it to the current Islamic education curriculum. Despite the fact that Indonesian FTFs to Syria have ceased since the defeat of ISIS, this paper argues that PEA, MA, and the Theory of Change can be used to analyse the future movement of Indonesian FTFs and to take preventative measures against it.